PENANAMAN NILAI-NILAI KARAKTER PADA PEMBELAJARAN TEMATIK BERMUATAN IPS SECARA DARING SISWA KELAS IV DI SDN KEPEK II SAPTOSARI GUNUNGKIDUL - Erlinda, Erlinda; Zulfiati, Heri Maria (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to describe: (1) The importance of instilling character values in bold learning, (2) instilling character values in thematic learning with social studies in a bold manner, (3) regulated constraints & solutions in instilling values characters in thematic learning with social studies in a bold manner. The research was conducted at SDN Kepek II Saptosari Gunungkidul for grade IV students (15 students). The research was conducted in January 2021. The data sources were the principal, fourth-grade teachers, parents & students. The data technique uses observation, interview, & documentation techniques. The research instruments were observation, interview, & documentation. Test the validity of the data using input, improve persistence, triangulate (source, technique, & time), & use reference materials. The data analysis technique uses Miles & Huberman analysis which consists of data collection, data reduction, data presentation, and data retrieval. The results showed that (1) instilling character values is very important so that students have good attitudes & behavior. (2) Instilling character values is done in learning activities & outside learning; character values that have been successfully instilled are religion, the enthusiasm of reading, discipline, responsibility, honesty, environmental care attitude, and social care attitude. (3) Obstacles that inform & the solution is that if the child does not have a smartphone, the children can take & collect assignments at school, the information is forwarded to other students' parents, the teacher visits the student's house, the teacher gives time to arrange assignments until 21.00 WIB, the teacher uses various learning media to help the students understand the material, teacher supervision is limited so that parents include their children in tutoring & TPA activities to support the instilling of character values in children.